Advances in self-learning in Brazil's educational system (Research, Society and Development, 2022)
Objective to know the influence of autodidactics in the educational system in Brazil. This is a qualitative, integrative literature review study. The analysis of the information resulted in two categories: Autodidaxia or Autodidact; Autodidaxia and digital technology in education. In ancient times the autodidact was a curious person, possessing minimal grammar and no diploma, who assumed self-learning and immersion in knowledge. All people, including the autodidact, need help and guidance from someone and materials to study. Self-learning is an immediate study solution, provided by access to various digital technologies that offer published materials on the most diverse subjects and from all over the world. Brazil adopts Distance Education (DL) in technical, undergraduate, and graduate courses using information technology with teacher supervision. Currently, the legal adoption of self-learning in the formal system of elementary and high school is being discussed.